Predicting Employees’ Happiness And Innovativeness Through The Lens Of Internal CSR Practices - Addi Muqit, Abdul Malik (2022)
CSR refers to corporate actions and policies that are meant to have a good impact on the world. CSR is based on the premise that businesses should seek additional pro-social goals in addition to achieving profits. Despite the development of CSR gaining some foothold in the world, the focus on employee-related CSR activities has still not been extensively researched. Internal CSR refers to the steps an organization takes to meet employee expectations, proactively meet and improve the fairness of an employees’ organization. The main idea behind internal CSR is to assist employees by providing fairness, increasing happiness, which can increase innovativeness in employees. This research intends to investigate the inter-relationship among Internal Corporate Social Responsibility practices (Internal CSR practices), employees’ happiness and employees’ innovativeness among employees in Malaysia during a pandemic. The results found that Internal CSR practices have a significant positive relationship with employees’ happiness and employees’ innovativeness. The relationship between employees’ happiness and employees’ innovativeness is also significantly positive. Furthermore, the most significant dimension for Internal CSR towards employees’ happiness is workplace diversity, while the most significant dimension for Internal CSR towards employees’ innovativeness is empowerment. This research provides useful information to organizations of the benefit in implementing internal CSR practices on employees’ happiness and innovativeness. Besides that, the findings will add value to the existing body of knowledge and to the organizational behaviour researchers. The potential benefits to humanity arise from the examination of the dimensions under Internal CSR practices, such as employment stability during a pandemic. All parties concerned would be able to reap the benefit by understanding the importance of Internal CSR practices.